18F-FDG PET/CT in Renal Infections: Evidence of Acute Pyelonephritis in a Horseshoe Kidney. (February 2017) - Morelle, Maxime; Jaillard, Alice; Bellevre, Dimitri; Collet, Guillaume; Petyt, Grégory
Abstract : Abstract: A 58-year-old paraplegic patient was prescribed 18 F-FDG for persistent inflammatory syndrome after aortic surgery for dissection. The examination was performed on a Siemens mCT Flow PET/CT and shows a moderate prostate uptake, related to prostatitis on self-catheterization and a focal renal cortical hypermetabolism of the left medial midpole of a horseshoe kidney, which corresponds to renal parenchyma on the CT, and suggests pyelonephritis, confirmed by 99m Tc-DMSA SPECT/CT.